2024
DOI: 10.1038/s41612-024-00583-8
|View full text |Cite
|
Sign up to set email alerts
|

Climate change linked to drought in Southern Madagascar

Angela Rigden,
Christopher Golden,
Duo Chan
et al.

Abstract: Southern Madagascar experienced a prolonged drought over the last five years, but whether these conditions are a manifestation of global climate change has been unclear. Here, we document trends beginning as early as 1980 towards a later rainy-season onset across three distinct remotely sensed indicators: precipitation, soil moisture, and vegetation greenness. All three indicators closely covary, particularly over the last decade when satellite observational resolution and accuracy is greatest. Furthermore, ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Madagascar is highly vulnerable to climate change, and, in 2020, drought impacted 1.3 million people ( 47 ). Recently, research has confirmed that global climate change is responsible for the increasing frequency and severity of droughts in Southern Madagascar ( 48 ). Given the challenges of poverty, food insecurity, climate change, and lack of mental health care specialists, it is likely that the mental health of the Malagasy population will worsen in the coming years without population-based mental health interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Madagascar is highly vulnerable to climate change, and, in 2020, drought impacted 1.3 million people ( 47 ). Recently, research has confirmed that global climate change is responsible for the increasing frequency and severity of droughts in Southern Madagascar ( 48 ). Given the challenges of poverty, food insecurity, climate change, and lack of mental health care specialists, it is likely that the mental health of the Malagasy population will worsen in the coming years without population-based mental health interventions.…”
Section: Introductionmentioning
confidence: 99%